Halal Certification: Improving Business Quality with Superior Islamic Ethics - Mardikaningsih, Rahayu; Chasanah, Uswatun (Metromedia, 2023)
Providing halal label certification on food products has become an effective means for consumers to more easily choose food that complies with halal principles. This is a form of producer responsibility in running a business and as a protection for consumers. However, consumers have the right to obtain clear and detailed information about each composition or ingredient used in the manufacture of the products they buy. The reason behind this need is because products circulating in the community cannot always be considered safe, especially for Muslim consumers. Therefore, the purpose of this paper is for producers and consumers to have an awareness of the importance of including halal labels and halal certification on every product they market in the community. In writing this article, the author uses a qualitative method of literature study The results obtained from this writing show that the awareness of producers was initially minimal, and consumers initially did not really consider the importance of halal labels. However, along with the widespread lifestyle that prioritizes halal principles, they began to realize how crucial halal certification is for food products.